THE CHALLENGES AND DIFFILCULTIES OF SINO-US MILITARY DIPLOMACY IN THE AFRICAN CONTINENT - F. Barbosa, Ailton Jose (European Scientific Journal, ESJ, 2014)
The Sino-US relationship is increasely intertwined and this article looks at the military presence of both nations in the African continent. In particular a look from the military present in the post-9/11 world, where the war on terror have been launch by US and where the African continent is see witnessing a rise on terrorism. The article also looks at the Sino-US military action in Africa from the perspective of trade and arms sales where the securitizing a shipping lanes and factories are becoming of great concern for both the Chinese and the Americans. The article also looks at the current race between the more established “Washington consensus, and the relative “Beijing consensus”. This race is taking part in Africa it is part of a bigger race which is for a unipolar and multipolar diplomatic world and the support of each African country is crucial. The Asian and the American contenders are using their military capability to secure support to different African political and institutions.